DESIGN OF THE ALAMOUTI SCHEME FOR A MIMO RECEIVER AND ITS IMPLEMENTATION ON AN FPGA - Silva, Jorge (2013)
This paper analyses the Alamouti scheme for different antenna configurations and different modulation types,namely BPSK, QPSK and QAM. All configurations were modeled and simulated in MATLAB. A MIMOreceiver for a 21 antenna configuration and BPSK modulation was implemented in a FPGA. The FPGAresults indicate that the Alamouti scheme is a good design option for hardware implementation of a MIMOreceiver. The receiver uses only about 10% of the resources of a medium-sized FPGA and achieves almost300 Msymbols per second.